Exploring the Digital Readiness of Underprivileged Secondary Schools in South Africa - (:unkn) unknown (My University, 2024)
This study explored the issue of digital readiness in underprivileged secondary schools in South Africa, delving into the complexities and challenges associated with technology integration in education. The study focused on understanding the relationships between the availability of infrastructure, the attitudes of teachers towards using technology in teaching, the effectiveness of technological implementation, and external challenges such as load shedding. The study adopted a qualitative case study approach, utilizing semi-structured interviews to gain insights from participants on their experiences, perceptions, and challenges related to technology usage in the classroom. The findings highlight the disparity in infrastructure availability, with many schools grappling with insufficient or outdated equipment. Additionally, the study uncovered different attitudes among teachers, with older educators showing a leaning toward traditional teaching methods despite acknowledging the potential benefits of technology. The challenges of integrating technology into the daily teaching routine are further compounded by the unpredictable nature of load shedding, which disrupts planned activities and hinders the consistent use of technological tools. In conclusion, the study emphasizes the critical need for a context-aware approach in improving the digital readiness of underprivileged schools, underscoring the importance of continuous teacher training, administrative support, and strategic partnerships for equipment donation. It contributes significantly to existing literature by providing insights specific to the South African context and lays a foundation for future research and policy initiatives aimed at fostering digital literacy and readiness in underprivileged educational settings.
Keywords: African Research